Aerobic and anaerobic training: effects on cognitive function in adolescents - Krivolapchuk, I. A.; Chernova, M. B. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the impact of bioenergetic factors on the physical performance of young athletes during cognitive tasks of different difficulty levels.